Comparative metabolomic profiling of Cupriavidus necator B-4383 revealed production of cupriachelin siderophores, one with activity against Cryptococcus neoformans - Ahmed, Mohammed M. A.; Tripathi, Siddarth K.; Boudreau, Paul D. (Frontiers in Chemistry, 2023)
Cupriavidus necator H16 is known to be a rich source of linear lipopeptide siderophores when grown under iron-depleted conditions; prior literature termed these compounds cupriachelins. These small molecules bear β-hydroxyaspartate moieties that contribute to a photoreduction of iron when bound as ferric cupriachelin. Here, we present structural assignment of cupriachelins from C. necator B-4383 grown under iron limitation. The characterization of B-4383 cupriachelins is based on MS/MS fragmentation analysis, which was confirmed by 1D- and 2D-NMR for the most abundant analog (1). The cupriachelin congeners distinguish these two strains with differences in the preferred lipid tail; however, our rigorous metabolomic investigation also revealed minor analogs with changes in the peptide core, hinting at a potential mechanism by which these siderophores may reduce biologically unavailable ferric iron (4–6). Antifungal screening of the C. necator B-4383 supernatant extract and the isolated cupriachelin analog (1) revealed inhibitory activity against Cryptococcus neoformans, with IC50 values of 16.6 and 3.2 μg/mL, respectively. This antifungal activity could be explained by the critical role of the iron acquisition pathway in the growth and pathogenesis of the C. neoformans fungal pathogen.